Pattern and implications of labour migration on technical efficiency of farm households: A study in Bundelkhand region of central India - R, ANUJA A; KAR, AMIT; KUMAR, PRAMOD; JHA, G K; BURMAN, R ROY; SINGH, K N; P, SHIVASWAMY G (The Indian Journal of Agricultural Sciences, 2020)
Labour migration and remittance influence resource use efficiency in agriculture. The present study evaluates the impact of labour migration on crop productivity and technical efficiency in the Bundelkhand region of central India. The study is based on a primary survey of 240 farm households, comprising 120 migrant and 120 non-migrant households during 2016-17.The average yield of selected crops was higher in non-migrant households than that of migrant households. However, there was no variation in the input use intensity between the two categories.Factors such as education, farming experience, and access to extension services significantly reduced technical inefficiency for migrant households.In addition to these factors, access to irrigation significantly reduced technical inefficiency for non-migrant households. Development of irrigation infrastructure and strengthening extension linkage can enhance crop productivity and check distress migration in the Bundelkhand region.